Elevated Serum Soluble Tim-3 in Primary Biliary Cholangitis: Lack of Correlation with Cytokines, Chemokines, and Clinical Parameters - Xu, Jiamin; Ma, Haitao; Dang, Futao; Lin, Hua; Zhang, Chenrui; Wang, Qian; Tan, Xu; Yang, Xian; Zhang, Jingyi; Bao, Weimin; Tang, Yingmei (Turkish Journal of Gastroenterology, 2025)
Background/Aims: Soluble Tim-3 (sTim-3) has been implicated in primary biliary cholangitis (PBC), an autoimmune liver disease, though its clinical significance remains unclear. This study aimed to evaluate the associations between sTim-3, Galectin-9, and cytokines in PBC, as well as their potential prognostic utility. Materials and Methods: A total of 55 PBC patients were enrolled (45 without overlapping conditions) and serum levels of sTim-3, Galectin-9, and 18 cytokines/chemokines were measured. Disease severity was assessed using the model for end-stage liver disease (MELD), MELD-Na, and Mayo risk score (MRS) 1994, alongside fibrosis-4 (FIB-4) index and monocyte-lymphocyte ratio (MLR). Patients were stratified by fibrosis stage, cirrhosis status, Child-Pugh score, and treatment duration, with intergroup parameter comparisons performed. The least absolute shrinkage and selection operator regression identified potential risk factors for MRS1994, followed by multivariate linear regression analysis. Results: Compared to healthy controls, PBC patients exhibited elevated sTim-3 and reduced Galectin-9, though neither biomarker cor related with clinical parameters. Advanced disease stages were associated with increased MLR, interferon-gamma (IFN-γ), interleukin (IL)-6, IL-8, C-C motif chemokine ligand 3 (CCL3), CCL20, and C-X3-C motif chemokine ligand 1 (CX3CL1). The MELD/MELD-Na scores strongly correlated with IL-6, TNF-α, IFN-γ, CCL3, and CCL20, while IL-6 and CX3CL1 linked to FIB-4 index. Multivariate analysis identi fied MLR, albumin/globulin (A/G) ratio, TNF-α, IL-6, and CX3CL1 as independent predictors of MRS1994. Conclusion: Although sTim-3 and Galectin-9 dysregulation lacked direct clinical relevance, MLR, A/G ratio, cirrhosis status, and inflam matory markers (TNF-α, IL-6, CX3CL1) emerged as robust predictors of disease severity (MELD) and prognosis (MRS1994), highlighting their potential for non-invasive risk stratification in PBC. Cite this article as: Xu J, Ma H, Dang F, et al. Elevated serum soluble tim-3 in primary biliary cholangitis: lack of correlation with cytokines, chemokines, and clinical parameters. Turk J Gastroenterol. Published online August 25, 2025. doi:10.5152/tjg.2025.24520.